TO THE QUESTION OF INTERCULTURAL UNDERSTANDING FROM THE POINT OF VIEW OF IDIOMS (Scientific journal of the Fergana State University, 2023)
The article examines a branch of vocabulary - idioms, as the most national and specific branch of the language. To the question of literal untranslatability of idioms, it  is described that an idiom as such is a lexical unit that does not have direct meaning